In vitro tests for drug hypersensitivity reactions: an ENDA/EAACI Drug Allergy Interest Group position paper. Issue 8 (25th May 2016) - Mayorga, C.; Celik, G.; Rouzaire, P.; Whitaker, P.; Bonadonna, P.; Rodrigues‐Cernadas, J.; Vultaggio, A.; Brockow, K.; Caubet, J. C.; Makowska, J.; Nakonechna, A.; Romano, A.; et al.
Abstract: Drug hypersensitivity reactions (DHRs) are a matter of great concern, both for outpatient and in hospital care. The evaluation of these patients is complex, because in vivo tests have a suboptimal sensitivity and can be time‐consuming, expensive and potentially risky, especially drug provocation tests. There are several currently available in vitro methods that can be classified into two main groups: those that help to characterize the active phase of the reaction and those that help to identify the culprit drug. The utility of these in vitro methods depends on the mechanisms involved, meaning that they cannot be used for the evaluation of all types of DHRs. Moreover, their effectiveness has not been defined by a consensus agreement between experts in the field. Thus, the European Network on Drug Allergy and Drug Allergy Interest Group of the European Academy of Allergy and Clinical Immunology has organized a task force to provide data and recommendations regarding the available in vitro methods for DHR diagnosis. We have found that although there are many in vitro tests, few of them can be given a recommendation of grade B or above mainly because there is a lack of well‐controlled studies, most information comes from small studies with few subjects and results are not always confirmed in later studies. Therefore, it is necessary to validate the currently available in vitro tests in a large series of well‐characterized patients with DHR and to develop new tests for diagnosis.